1998
DOI: 10.1111/j.1467-9477.1998.tb00002.x
|View full text |Cite
|
Sign up to set email alerts
|

Immigrants in the Political Process

Abstract: Immigrants, who comprise a growing group in many European countries, are usually under‐represented in the political process. Sweden's immigrant policy, with its far‐reaching social and political rights, liberal citizenship laws and respect for cultural differences, is often regarded as an exemplary model of how to integrate immigrants in society. The 1975 electoral reform in Sweden gave immigrants the opportunity to become active in the democratic process by allowing foreign citizens to vote in local political… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 4 publications
2
13
0
Order By: Relevance
“…In order to make the result more intuitive, the coefficients can be converted from logged odds to odds ratios by exponentiation of the β coefficient. The result then indicates an odds ratio of .55, predicting that the odds of voting decreases by .45 for immigrants in comparison to natives, which is similar to the gap in electoral participation between immigrants and natives found in previous studies (Bäck and Soininen 1998;Jiménez 2011). I continue by testing H1, proposing a mobilising influence of public contextual hostility among immigrant residents.…”
Section: Resultssupporting
confidence: 82%
“…In order to make the result more intuitive, the coefficients can be converted from logged odds to odds ratios by exponentiation of the β coefficient. The result then indicates an odds ratio of .55, predicting that the odds of voting decreases by .45 for immigrants in comparison to natives, which is similar to the gap in electoral participation between immigrants and natives found in previous studies (Bäck and Soininen 1998;Jiménez 2011). I continue by testing H1, proposing a mobilising influence of public contextual hostility among immigrant residents.…”
Section: Resultssupporting
confidence: 82%
“…Finally, existing research suggests that, if anything, changes in immigrant representation drive immigrant turnout. Scholars have found that immigrant candidates in Sweden tend to mobilize the co-ethnic vote (Blomqvist 2000; 2004; Schierenbeck and Schütt 2004), and that knowing that fellow countrymen run for office has a strong positive effect on turnout among immigrants (Bäck 2004).
FIGURE 7. Native and Foreign-Born Voter Turnout in Municipal Elections as a Share of Each Sub-Population
…”
Section: Is Discrimination An Important Driver Of the Representation mentioning
confidence: 99%
“…In the developed democracies of Western Europe, residents of foreign origin tend to be less active in political life than the native population (Togeby 2004; Fennema & Tillie 2001; Adman & Strömblad 2000; Bäck & Soininen 1998). Given this state of affairs, it should be both empirically and theoretically important to investigate under what conditions immigrant associations may provide resources, motivation and – ultimately – political power to its members.…”
Section: Introductionmentioning
confidence: 92%